Towards Pax Sinica? China's rise and transformation : impacts and implications - Yeoh, Emile Kok-Kheng (Institute of China Studies, 2009)
This book examines and critically analyzes the regional political and economical implications of the rise of China from the perspectives of her Northeast and Southeast Asian neighbours, the rural and urban developmental dilemmas and challenges the Asian giant is facing on the domestic front, as well as the future of the country's continued odyssey of development, modernization and reform against the backdrop of consequential policy responses at momentous critical junctures and subsequent State policy development within the context of the exigencies engendered by ethnoterritoriality and the interplay of the central State and peripheral nationalism.